Spontaneous Flora as Reservoir for the Survival and Spread of the Almond Anthracnose Pathogen (Colletotrichum godetiae) in Intensive Almond Orchards - Madalena Ramos; Rodrigo Maurício; Vicelina Sousa; Pedro Talhinhas (Plants)
Almond anthracnose, primarily caused by Colletotrichum godetiae, severely affects intensively irrigated almond orchards. This polyphagous pathogen is dispersed among plants by rain splashes. Consequently, weeds may contribute to the survival and dispersal of the inoculum during the almond tree’s dormant period. This study investigated how C. godetiae interacts with plants from various species in the spontaneous flora of almond orchards and how these plant species may influence the maintenance and spread of inoculum and the disease. After inoculating a collection of plants with C. godetiae conidia, it was observed that the fungus can cause symptoms and signs on Lathyrus tingitanus and on Trifolium pratense and act as an epiphyte with the ability to maintain and multiply conidia on Conyza canadensis, Medicago orbicularis, Polygonum aviculare, Scorpiurus sulcatus, Taraxacum officinale, and Trifolium vesiculosum, thus contributing to the survival and multiplication of the inoculum. Conidia germinated and produced appressoria on Andryala integrifolia, Cichorium intybus, Medicago polymorpha, Medicago sativa, Torilis arvensis, Picris echioides, and Rumex pulcher, but no further development was detected, suggesting that these plants may limit the spread of the pathogen. A better understanding of the susceptibility of almond orchard flora will support optimized vegetation management to reduce inoculum reservoirs.